Intermarium as One of the Future European Image of Ukraine - Mykhailo Boichenko (International Society of Philosophy and Cosmology, 2020)
The Intermarium project is one of the most controversial and complex regional integration projects of Ukraine's European integration. The article proves that this project most accurately expresses the totality of common values and meanings that Ukrainians share with their closest neighboring countries. An attempt was made to give an integrative philosophical assessment to all the arguments in favor of the Intermarium project and its prospects for development in Ukraine. The Intermarium appears as one of the Future European Image of Ukraine, more alternative to the Eurasian project, but more complementary to the European Union project. The main arguments in favor of the Intermarium are, however, internal arguments rather than opposition to other projects of interstate integration. The Intermarium aims at preserving and developing the common cultural heritage of the countries of Central and Eastern Europe, as well as at developing and protecting their common economic, political, and other values. Territorial Neighborhood only creates certain prerequisites that can be used, and may or may not be used to create a neighborhood of value, that is, to form a common life world. This can happen and be maintained just if it will be provided, properly, and successfully implemented all components of the territorial neighborhood, such as geographical proximity, similarity of climatic conditions, use of common natural resources, creation of favorable conditions for cross-border cooperation, etc. The common regional values and meanings for the Intermarium should be protected by a joint effort - so that in any other format, larger